I︠A︡kornyi︠a︡ mi︠e︡sta v Beringovom mori︠e︡ / Kopirovalʺ khim. tush. Elʹshinʺ - Soviet Union. Gidrograficheskoe upravlenie; (Leningrad : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenie SSSR; [Ленинград] : Морское министерство, Главное гидрографическое управление СССР, 1925)
Malai︠a︡ korrekt. IX-1914 g. -- Bolʹsh. korr. IX-1923 g. Pechatano vʺ 1925 g; Малая коррект. IX-1914 г. -- Больш. корр. IX-1923 г. Печатано въ 1925 г.; Relief shown by hachures and spot heights. Depths shown by soundings and isolines.; Main title translation: Anchorage places in the Bering Sea.; Top margin title translation: Eastern Sea, Bering Sea.; Translation of map titles: Lavrentiya Bay (Saint Lawrence Bay) in the Bering Strait -- Bay of Provideniya in the Bering Strait -- Gulf of Tkachen (Butakova) -- Bay of Vestnik (on the Kamchatka Peninsula and Cape Zhelty) -- Plover Anchorage (in Provideniya Bay) -- Slavyanka Harbor (in Plover Bay).; Maps: Zalivʺ sv. Lavrentīi︠a︡ vʺ Beringovomʺ prolivi︠e︡ -- Bukhta Providi︠e︡nīi︠a︡ vʺ Beringovomʺ mori︠e︡ -- Zalivʺ Tkachenʺ (zaliv Butakova) -- Bukhta Vi︠e︡stnikʺ (na poluostrovi︠e︡ Kamchatka u mysa Zheltyĭ) -- Reĭdʺ Ploverʺ (vʺ bukhti︠e︡ providi︠e︡nīi︠a︡) -- Gavanʹ Slavi︠a︡nka (vʺ bukhti︠e︡ Ploverʺ).; Greenwich meridian.; "No. 551" -- corner margins Color;